A classification of the geothermal vegetation of the Taupō Volcanic Zone, New Zealand. Issue 1 (2nd January 2018) - Smale, Mark C.; Wiser, Susan K.; Bergin, Michael J.; Fitzgerald, Neil B.
ABSTRACT: We undertook stratified random sampling of vegetation, soil chemical fertility and subsurface soil temperature at 38 sites on 15 geothermal fields in the Taupō Volcanic Zone, central North Island, New Zealand, to develop a quantitative classification of geothermal vegetation types and to identify the main environmental drivers of vegetation composition. We implemented this with the fuzzy classification framework of noise clustering. Gradients in composition were derived using Detrended Correspondence Analysis ordination and related to soil physical and chemical parameters using correlation. Of 166 plant species recorded, only seven native species were present in > 20% of plots and only four adventive species in > 5% of plots. Subsurface soil temperatures ranged from ambient (7 °C) to near-boiling (98.5 °C). Classification identified 16 vegetation associations, almost all dominated by indigenous species and unique to geothermal fields. Subsurface soil temperature was the main factor controlling vegetation composition; soil chemistry was less important.